Molecular Characterization Of Listeria Spp. Isolated From Beef, Chicken And Fermented Fish In Malaysia - Rahayuningsih, Hajjah Endang purwati (2003)
Modified FDA method was found to give higher recovery of Listeria spp. than USDA method for different sources. The results indicated that the imported frozen beef samples from wet market examined were contaminated by seven different Listeria spp. namely, L. monocytogenes, L. ivanovii, L. seeligeri, L. innocua, L . welshimeri, L. grayi and L. murrayi. However, the use of FDA, USDA and the modified USDA methods may be more beneficial where a limited range of Listeria spp. to be recovered (L. monocytogenes, L. ivanovii and L . innocua). Listeria spp. was not isolated from any of the 23 samples of imported frozen beef from supermarket and from the five samples of buffalo meat examined. A total of two hundred and seventy isolates of Listeria spp. from different sources were investigated for their susceptibility to 18 antibiotics and were screened for plasmid profiles. Antibiotic susceptibility analysis revealed that all Listeria spp. isolates were resistant to two or more antibiotic (MAR 0 . 11 to 0.66). Majority of the 52 isolates of L. monocytogenes displayed resistance to bacitracin , ceptazidime, nalidixic acid , sulfamethazole. However, none were resistant to norfloxacin. Plasmid was detected in 9 (81.8%) of 11 strains of L. murrayi, 12 (80%) of 15 strains of L . grayi, 29 (55.8%) of 52 strains of L. monocytogenes, 8(50%) of 16 strains of L. denitrificans, 25 (41 .7%) of 60 strains of L. ivanovii, 25 (37.9%) of 66 strains of L.innocua), 13 (31 %) of 42 strains of L. welshimeri and 1 (1 2.5% ) of 8 strains of L. seeligeri. The plasmid sizes ranged from 2.7 to 54 Kb.